Development of minimast antenna system in base transmission station - Hussain, Muhammad Sabir (2012)
Presently the cellular mobile technology is widely used as the major means of communication world wide. The day by day increasing demand has resulted in an incessant growth of traffic in cellular mobile communication system. For the successful use of cellular mobile technology, the designing in the coverage of antennas and signal time delay are the major technical challenges. Its difficulty is further accentuated due to the eternally limited availability of radio spectrum. For ultra dense urban environments where the cell site antennas are placed well below the rooftops of surrounding building, some innovative network architectures have been presented. This thesis discusses the development of Minimast using the uplink and downlink performance of the Base Transmission Station (BTS) and air interference of antenna’s were used to cover the growth of traffic in cellular mobile communication system. The height of Minimast antenna was 20m and three antennas erected on it including one microwave with the frequency range of 2.3-2.4GHz. It was analyzed to determine the signal flows from BTS to antenna’s and the usefulness of this design for radio frequency (RF) signals. A Radio Frequency Unit (RFU-C) System was fixed inside the BTS to connect fibre optic cable, microwave and Minimast design. The signals travelled from BTS to Minimast to cover the area using RFU-C System. It is measured that time duration of the signal flow was much lesser (25m) than the tower or monopole design in addition its comparitively lower cost. The results from the Minimast design clearly shows that the voltage standing wave ratio value of 1.21 at frequency 2.4 GHz is better than the previous value of voltage standing wave ratio at frequency 2.4 GHz is 1.08 using tower design. Moreover, Minimast design has lower height, covers more area of cellular system, less distorted signals and can be troubleshooted using Handheld 32-bit software.